Program Kader Kesehatan Jiwa sebagai Pelaksanaan Upaya Kesehatan Jiwa - Dian Wahyu Hastari; Tri Kurniati Ambarini (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
This study aims to report on the development of mental health workers as part of mental health efforts in primary health care, specifically Community Health Centers (PKM). As the frontline of health services, PKM plays a crucial role in the handling and management of mental health issues in the community. However, not all mental health disorders are optimally reported. Data shows that the number of mental health disorder cases continues to increase annually, while only around 50% are successfully treated. Contributing factors include limited access to services and the uneven distribution of mental health workers. To address these issues, a mental health cadre program was developed. This program is designed to facilitate requests for mental health services through reporting, indexing, outreach, and home visits to patients. Cadres also act as liaisons between patients and primary health care services. The implementation phase begins with a needs assessment through interviews with health workers, patients, and community representatives. Next, selection is carried out based on cadre criteria, followed by recruitment and cognitive behavioral training. Training materials include knowledge of mental disorders, screening techniques, first aid, and evaluation methods. The results of the study using the 4-Level Evaluation Model indicate that the cadres are highly enthusiastic about their new role. There was a significant increase in knowledge between before and after cognitive behavioral training (p<0.001). Furthermore, the number of reported cases of mental health disorders increased, and the program was shown to align with the mission of primary healthcare services. Therefore, the formation of mental health cadres is considered effective in assisting healthcare workers in detecting and identifying patients with mental health problems in the Community Health Center (PKM) work area.